In Vitro Assay for Site-Specific Proteases Using Bead-Attached GFP Substrate. (November 2001) - Patel, Daksha; Frelinger, John; Goudsmit, Jaap; Kim, Baek
Site-specific proteases, which catalyze cleavage of peptide bonds in specific amino acid sequences of target proteins, play important roles in various biological events of many living organisms. In humans, disruption in regulation of these site-specific proteases can lead to pathological consequences. Here, we report a simple in vitro assay for enzymatic activities of site-specific proteases. This assay system employs a protein substrate molecule that is comprised of (i) His-tag binding module, (ii) cleavage sites, and (iii) green fluorescent protein (GFP) detection module. In this study, prostate-specific antigen (PSA) and Thrombin-specific cleavage sites were introduced into the substrate molecules. The overexpressed GFP substrate protein was purified with the aid of Ni ++ -charged magnetic beads. On cleavage by either PSA or Thrombin, GFP was released from the bound magnetic beads, enabling a direct measurement of the cleaved product by fluorescence. Detection sensitivity, as well as the kinetics of reaction of PSA cleavage with the GFP substrate, was similar or better than commercially available PSA fluorogenic peptide substrate. This bead-attached GFP substrate was also used for an inhibition assay using a competitive inhibitor of Thrombin. In conclusion, this assay offers a simple fluorescent method for monitoring the activity of the site-specific proteases. Furthermore, this system provides flexible means of incorporating varying sizes of flanking sequences adjacent to the cleavage site, which can be essential for studying the regulatory macromolecular interactions between proteases and their substrates.